Soyfood consumption and risk of glycosuria in post-menopausal women - Nurmillah, Nurmillah; Yolantha, Irena Stafani; Livinus, Victor (Faculty of Medicine, Trisakti University, 2010)
Menopause is a natural event to be experienced by every woman and appears to be associated with increased risk for developing type 2 diabetes mellitus. It has been postulated that a diet high in legumes may be beneficial for the prevention of glycosuria. These unique components of soy have been shown to have beneficial effects on glucose and insulin homeostasis. The objective of the present study was to examine the possibility of an association between soy food consumption and risk of glycosuria in postmenopausal women. A cross-sectional study was conducted among 94 postmenopausal women attending Mampang Prapatan Health Center, Mampang Prapatan subdistrict, South Jakarta. Anthropometric measurements were taken using standard instruments and dietary intake was assessed with a validated food-frequency questionnaire. A dipstick semiquantitative assay for urinary glucose was used to define glycosuria (positive). The results showed that 12.8% of postmenopausal women had glycosuria and mean isoflavone intake was 69.5 Â± 61.4 g/d. Intake of isoflavone was inversely associated with risk of glycosuria. Compared to women in the lowest quintile of isoflavone intake (Q1), postmenopausal women in the highest quintile (Q5) had a lower risk for glycosuria of 0.30 times that of Q1, which risk was however statistically not significant (OR = 0.30; 95% CI = 0.02 â€“ 3.14). In conclusion, isoflavone may play a role in the prevention of glycosuria (an important indicator of diabetes) among postmenopausal women.